Globalization And Higher Education Institutions: Opportunities and Challenges for Academic Institutions in Implementing ITC - Dr. M. S. Sibi, Dr. K. A. Arokiaraj, Renjith M; Dr. Chandrika Reddy, Dr. R. Tamilselvi, Dr. K. Prakash (Journal of Informatics Education and Research, 2024)
India's educational path has changed dramatically over the years, moving from traditional mentoring and learning practices to creating the second-largest higher education system in the world. The swift development of Information Technology (IT) has accelerated this shift and brought about significant adjustments in the fields of education, services, employment, and business operations. By removing prior barriers, the integration of information, technology, and communication (ICT) within the educational domain has significantly transformed access to learning resources, knowledge, and information. The Covid-19 pandemic's outbreak sped up the adoption of ICT and made it necessary to switch from traditional in-person instruction to remote learning methods during lockdowns. This shift brought with it a multitude of opportunities and difficulties in addition to broadening the scope and adaptability of postsecondary education. This study carefully analyzes the state of IT integration in higher education today, outlining both the benefits and drawbacks of this approach. The study used a quantitative methodology, with questionnaires serving as the main methodological instrument. 86 instructors connected to an Indian university took part in the survey as responders. This study offers important insights for policymakers, educators, and stakeholders to manage the difficulties of the integration in higher education by critically analyzing both the benefits and obstacles. The ultimate goal is to support strategic planning and well-informed decision-making to fully utilize ICT for the advancement of higher education in India and abroad.